Due umili verghiani. Strategie della soggettivazione in Rosso Malpelo e Jeli il pastore - Scaravilli, Guido (Status Quaestionis, 2023)
In their theory, the naturalists excluded the possibility of representing inner lives of the characters of the Fourth Estate. However, narrative practice reveals a different scenario. In the two analyzed short stories of Giovanni Verga, Rosso Malpelo and Jeli il pastore, it is shown that, in the case of the two protagonists, Verga resorts to elegiac forms to delineate their primitive and ferocious psychology.